Hip Active Range of Motion in Patients with Femoroacetabular Impingement Syndrome - Łukasz Stołowski; Gino Kerkhoffs; Tomasz Piontek (Sensors)
Femoroacetabular impingement syndrome (FAIS) is characterized by hip pain and restricted range of motion (ROM), typically due to structural conflict between the femoral neck and the acetabulum. This study aimed to quantify active ROM limitations in FAIS patients, comparing them with healthy controls to establish normative values, particularly in non-conflicting directions. Methods: A total of 53 FAIS patients scheduled for hip arthroscopy were compared to 49 healthy matched controls. Active ROM was assessed using inertial measurement unit (IMU) sensors, with measurements taken in standing and prone positions. Outcomes included flexion, external rotation, internal rotation, and total rotation ROM, alongside demographic and radiographic data. Gender-based ROM differences were also analyzed. Results: FAIS patients demonstrated significant reductions in flexion, internal rotation, and total rotation ROM in the involved hip, with large effect sizes, while external rotation remained unaffected. ROM in the uninvolved hip was also lower than in controls but showed increased external rotation. Gender differences were observed, with females exhibiting significantly higher internal rotation and, in healthy controls, greater total rotation than males. Conclusions: FAIS patients have significant active ROM restrictions in non-conflicting directions, suggesting broader joint limitations potentially tied to early hip osteoarthritis or capsular and musculoskeletal adaptations. Gender differences highlight the importance of individualized ROM assessment. This study introduces IMU-based ROM evaluation as a promising tool for diagnosing and monitoring FAIS, providing insights into functional impairments that can be used to guide targeted interventions.